OS ESCRITOS DE ELLEN GOULD WHITE: MANIPULAÇÃO MEN-TAL, CONTROLE COMPORTAMENTAL E VENERAÇÃO DO LÍDER - MEDEIROS, ALEXANDRE (2019)
This research intends to analyze worldviews around spirituality and its relations with the world. I will explore through the anthropological paths proposed by Jack David Eller, the religious views that regard the world, pleasure, daily life, art and beauty as enemies to be fought by rigid and inflexible ascetics. To do so, I will thematically focus - as a representative type - the speeches of Ellen G. White. In this case, I will investigate the "theoretical" basis that surrounds this discourse and that allows to govern the communities that follow the charismatic leadership that (in) form the movement or cult in question. Such support, we will gather from the analyzes of the anthropologists Charles Lindholm, Emerson Giumbelli and the philosopher of education Jean Lauand, that allow the com-prehension in broader context of proposals as of Ellen Gould White.